FORMATION OF AN OPTIMIZED MODEL OF WORK IN THE NON-GOVERNMENTAL SECTOR - Bakardzhieva, Krasimira (E-Journal VFU, 2025)
The aim of this article is to propose a new method for informal training of workers in the non-governmental sector. Developed in the context of design thinking, the method focuses on recognizing the strengths and weaknesses of people working in voluntary organizations by incorporating self-assessment, or self-evaluation. It was demonstrated in 10 countries. It refers to the self-knowledge of participants, acquired from their real experience in the organization, the assessment of their own role in it and the improvement of achievementsin achieving goals, through a professionally made decision. We discussed the possibility of expanding and applying the method to other sectors that are related to decision-making with the active participation of workers.
Keywords: design thinking; skills; self-assessment; organizational learning